2000
DOI: 10.1080/000164800454026
|View full text |Cite
|
Sign up to set email alerts
|

Lasting Effects of Otitis Media with Effusion on Language Skills and Listening Performance

Abstract: Klausen O, Møller P, Holmefjord A, Reisaeter S, Asbjørnsen A. Lasting effects of otitis media with effusion on language skills and listening performance. Acta Otolaryngol 2000; Suppl 543: 73 -76.Otitis media with effusion (OME) and its related hearing loss has been associated with delayed language development, particularly if the disease is recurrent or of long duration. To find out more about the long-term effects of OME on language skills and listening performance we performed a retrospective study. A group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 9 publications
1
37
0
7
Order By: Relevance
“…5 Asbjornsen et al 3 applied a dichotic consonantvowel test and found that the group with a history of otitis media performed worse in sustaining attention to auditory events, which was similar to our findings. Klausen et al 33 used a similar dichotic consonant-vowel test and concluded that OME affects the ability to persist and focus attention on auditory events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Asbjornsen et al 3 applied a dichotic consonantvowel test and found that the group with a history of otitis media performed worse in sustaining attention to auditory events, which was similar to our findings. Klausen et al 33 used a similar dichotic consonant-vowel test and concluded that OME affects the ability to persist and focus attention on auditory events.…”
Section: Discussionmentioning
confidence: 99%
“…The type of attentiveness that was assessed is not always specified, and is done by assessing the behavior of children; [24][25][26][27][28][29] other studies use individual tests to evaluate a specific type of attention. [30][31][32][33] Attention difficulties have been reported in subjects with reading impairment, 34 dyslexia, 35 aphasia, 36 sclerosis, 37 ADHD, 38 APD, 39 sleep deprivation,40 and cleft lip and palate. 32,28 Studies relating sustained auditory attentiveness and cleft lip and palate were not found in our review; we thus tried to correlate this study with those that included subjects with a history of recurring otitis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several studies have shown that persistent and/or recurrent OME in childhood may have detrimental effects on hearing, behaviour and speech or language development. Thus, OME is a topic for concern, which requires prevention and treatment [6][7][8][9]. Early identification of groups with a high risk of recurrent OME would enable care providers to apply efficient treatment policies.…”
Section: Introductionmentioning
confidence: 99%
“…Children suffering from otitis media with effusion were reevaluated one or more months later, after effusion was resolved. If effusion persisted for more than 2 months, audiologic examination was performed taking into consideration the changes brought by otits media with effusion on audiometric measurements [27][28][29]. A flow chat of the protocol is presented in Fig.…”
Section: Methodsmentioning
confidence: 99%